Valproic acid targets IDH1 mutants through alteration of lipid metabolism - Lubayna S. Elahi; Michael C. Condro; Riki Kawaguchi; Yue Qin; Alvaro G. Alvarado; Brandon Gruender; Haocheng Qi; Tie Li; Albert Lai; Maria G. Castro; Pedro R. Lowenstein; Matthew C. Garrett; et al. (npj Metabolic Health and Disease)
Abstract Histone deacetylases (HDACs) have a wide range of targets and can rewire both the chromatin and lipidome of cancer cells. In this study, we show that valproic acid (VPA), a brain penetrant anti-seizure medication and histone deacetylase inhibitor, inhibits the growth of IDH1 mutant tumors in vivo and in vitro, with at least some selectivity over IDH1 wild-type tumors. Surprisingly, genes upregulated by VPA showed no enhanced chromatin accessibility at the promoter, but there was a correlation between VPA-downregulated genes and diminished promoter chromatin accessibility. VPA inhibited the transcription of lipogenic genes and these lipogenic genes showed significant decreases in promoter chromatin accessibility only in the IDH1 MT glioma cell lines tested. VPA inhibited the mTOR pathway and a key lipogenic gene, fatty acid synthase (FASN). Both VPA and a selective FASN inhibitor TVB-2640 rewired the lipidome and promoted apoptosis in an IDH1 MT but not in an IDH1 WT glioma cell line. We further find that HDACs are involved in the regulation of lipogenic genes and HDAC6 is particularly important for the regulation of FASN in IDH1 MT glioma. Finally, we show that FASN knockdown alone and VPA in combination with FASN knockdown significantly improved the survival of mice in an IDH1 MT primary orthotopic xenograft model in vivo. We conclude that targeting fatty acid metabolism through HDAC inhibition and/or FASN inhibition may be a novel therapeutic opportunity in IDH1 mutant gliomas.